The effectiveness of budgeting and budgetary control system as a management control device - Ali, Zainab (1991)
A budget is not simply an estimate or a prediction but it is a management plan expressed in quantative values. A budgetary control is to provide a basis for monitoring the progress of the organisation in order to achieve the objectives. This study was conducted to evaluate the effectiveness of budgeting and budgetary control as a device for management control. data and information were collected from relevant journals and articles. One organisation has been selected as a model to collect primary information through interview.